Utilisation of triticale (X Triticosecale Wittmack) and residual oat flour in breadmaking - Anna Fraś; Kinga Gołębiewska; Damian Gołębiewski; Magdalena Wiśniewska; Marlena Gzowska; Dariusz R. Mańkowski (Czech Journal of Food Sciences, 2021)
During the last few years, non-bread cereals, as a rich source of bioactive components, play an increasingly important role in the production of new healthier food. A large number of diet-related diseases in society requires developing and regular consumption of high-quality food. In this study, triticale flour was supplemented with residual oat flour (ROF), which is a by-product in the production of oat fibre concentrate, to obtain triticale-oat bread with improved chemical composition and quality. The flours obtained from 3 winter triticale cultivars were enriched with 10%, 15%, and 20% of ROF. An increasing level of ROF resulted in higher protein and lipids content and a two-fold increase in β-glucan content (from 0.3% for control breads to 0.6% for 20% ROF) what improved the quality of dietary fibre in breads (DF). The bread parameters, especially bread volume (BV), the shape of loaves, crust colour and crumb texture, decreased with the addition of ROF. The triticale-oat breads with the best quality were obtained from 10% addition of ROF. Results confirmed the possibility of utilisation triticale and ROF for the production of bread with a unique chemical composition constituting a simultaneously rich source of DF.